The Influence Of Competence And Accountability On The Performance Of Village Employees Is Mediated By Organizational Commitment In Serang Baru District, Bekasi Regency - Sintia Arsita; Fitri Rezeki; Retno Purwani Setyaningrum (Dinasti International Journal of Education Management And Social Science, 2024)
Village community empowerment aims to enable villages to carry out joint actions as a unit of village governance. The unity of governance of village community institutions and customary institutions, as well as the unity of economic and environmental governance. This breakthrough makes the village the spearhead of development that has autonomy to prosper its people with the enactment of village autonomy. Villages can organize government independently based on, by and for the people. The purpose of this study is to determine the influence of competence, performance and community participation on the performance of village apparatus and whether organizational commitment can mediate competence and accountability to performance in Serang Baru District, Bekasi Regency. This research method is quantitative by distributing questionnaires and the results are processed using SmartPLS 3.0. The results of the study are that competence and accountability respectively have a significant effect on performance. Organizational commitment is able to mediate between the influence of competence on performance and accountability on performance.